Sanksi Pidana Terhadap Pelaku Tindak Pidana Pajak Penghasilan - Kadek Hendra Wiguna; Ida Ayu Putu Widiati; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2025)
Income tax is a direct tax levied by the central and state governments. The problem formulations in this study include: 1. How are income tax offenses regulated? What are the penalties for income tax violators? The research method applied in this research is normative legal research, using a statutory approach and case studies. Based on the results of the research, it can be concluded that Law Number 36 of 2008 concerning Income Tax has regulated the principles of calculating income tax such as who is subject to tax, what is the purpose of the tax, and different applicable tax rates. Violations of laws and regulations in the field of taxation committed by taxpayers are regulated in Articles 38 and 39 of Law Number 28 of 2007 concerning General Regulations and Procedures for Taxation, as well as Article 43A of Law Number 7 of 2007 In tax law, criminal sanctions apply, including fines, imprisonment, and confinement. The use or management of administrative and criminal sanctions in the field of taxation is explained in Law Number 28 of 2007 concerning General Regulations and Tax Procedures as stated in Articles 38 and 39.